Pemanfaatan Limbah Budidaya Ikan Lele Dengan Sistem Akuaponik Di Kelurahan Gedog - Yessy Risma Priranti; Rizky Ramadhani; Aldia Safira Hartono; Nabila Zafirna Syazwani; Aprilia Retnowati; Dewi Puspa Arum (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The Women Farmers Group (KWT) “Guyub Rukun” in Gedog Village has the potential to produce vegetables using an aquaponics system. This is supported by the large amount of waste from catfish farming. Utilization of catfish farming waste is still not optimal. The use of catfish farming waste from the Women Farmers Group (KWT)